Inclusive or Divisive Choices? Education Policy Preferences in the Bilingual Education System of Estonia. Issue 1 (2nd January 2023) - Lauri, Triin; Põder, Kaire
ABSTRACT: This article investigates educational preferences in the bilingual education system that reinforce the salience of both socio-economic and socio-cultural issues. We ask, first, how many distinct groups of educational preferences exist and whether these differ by ethnic nationality. Second, we investigate the extent to which economic self-interest vs values-driven logic of preference formations explain educational preferences and whether these determinants differ by ethnic nationality. We rely on individual-level survey data and run Latent Class Analysis and multivariate regression. We find three distinctive classes of educational preferences and that relatively high popular demand for private provision and parental choice co-exist alongside respect for comprehensive schooling in Estonia. These classes differ slightly by ethnic nationality – Russians show relatively more support for inclusive choice, while Estonians show greater support for public comprehensive schooling, with only weak socioeconomic and political party influences. The only clear explanation for different latent-class belonging is values, i.e., belief in meritocracy and the fairness perception of educational inequality; somewhat surprisingly, the marginal effects of these do not differ by ethnic nationality.